The Influence of Social Intelligence, Learning Behavior, Culture and Interest in Learning on the Level of Accounting Understanding Moderated By Self Confidence: Pengaruh Kecerdasan Sosial, Perilaku Belajar, Budaya dan Minat Belajar Terhadap Tingkat Pemahaman Akuntansi Yang Dimoderasi Oleh Percaya Diri - Dian Irmayanti; Wiwit Hariyanto (Universitas Muhammadiyah Sidoarjo, 2021)
Thisi studyi aimsi toi determinei thei moderatingi rolei ofi Selfi Confidencei in thei relationship ofi Social Intelligence, Learning Behavior, Culture, and Interest in Learning to the Level of Accounting Understanding. Thisi studyi usesi ai quantitativei approach.i Thei samplingi techniquei usedi is simple random isampling iwith probability sampling by distributing 203 questionnaires to students of the accounting study program at Muhammadiyah University of Sidoarjo. The data analysis technique used is the iOuter iModel ito testi thei validityi and ireliability of the data and the Inner Model to test the hypothesis iusing the iSmartPLS versioni 3.0 program.ii Thei resultsi ofi thisi studyi indicatei that:i 1)i Self-confidence cannot moderate the relationship between Social Intelligence as evidenced by the p value of 0.560 and ithe t-statistic value of 0.584. 2) iSelf-confidence ican imoderate ithe relationshipi betweeni Learningi Behaviori andi Accountingi Understandingi Level and this is evidenced by the results of the p value of 0.046 and the t-statistic value of 2.003. 3) Self-confidence cannot moderate the relationship between culture as evidenced by the p value of 0.726 and the t-statistic value of 0.350. 4) Self-confidence cannot moderate the relationship between learning interest as evidenced by the p value of 0.146 and the t-statistic value of 1.457.